Оптимизация элементов теплоутилизационных систем энергетических установок - Степанова, О (Енергетика і автоматика, 2017)
Extended resume the article Stepanova A. ОPTIMIZATION OF ELEMENTS OF HEAT RECOVERY OF POWER PLANTS The analysis of various aspects of optimization of heat recovery systems of power plants is carried out. The feasibility of developing new evaluation criteria of efficiency, which can serve as optimization objective is noted. Methods, which are used for functional dependencies objective functions to optimize the parameters of the individual elements of heat recovery systems, are established. Rational choice of optimization methods improves its effectiveness, since it allows the use when designing the installation parameters, as close to the optimal settings. For functional dependencies criteria of efficiency, heat recovery units on the parameters examined following methods. • Balance method of exergy analysis. • The methods of thermodynamics of irreversible processes, combined with exergy methods. • Statistical methods of planning the experiment. Balance methods involve drawing up of exergycal, thermal and material balance equations, supplemented by the relevant hydrodynamic equations and the heat-transfear equation. On the basis of these methods for gas-termoutilizato-ditch, Members of the heat recovery system of glass furnaces, it is obtained the functional dependence of the objective function to optimize the parameters of the heat recovery units. The heat recovery boiler installations intended for heating and humidifying the air blast, heat exchanger glass -indigenous furnaces are used as a coolant multiphase medium with taking into account concentrations of one or more phases. Such coolants may be dusty wet flue gases, which alter the moisture content and the degree of dust during the passage through the heat exchanger. In such multiphase flow exist simultaneously different thermodynamic forces and they cause irreversible flows. This allows the search for functional dependencies required for solving optimization problems using methods of thermodynamics of irreversible processes, together with exergy methods. For these cases, a three-phase macroscopic thermodynamic model has been formulated for variable mass system when the concentration of one of the phases, and the differential equation of exergy balance. By using statistical methods for planning experiments obtained functional dependence exergetic efficiency criteria on the structural parameters of the heat exchange surface of the contact plate heater included in the heat recovery system of the boiler plant. On the basis of functional relationships studied patterns of influence of parameters studied teploutilizator their exergy efficiency and the optimal values of these parameters.